PENGARUH SERVICE QUALITY, PRODUCT QUALITY DAN PERCEIVED VALUE TERHADAP KEPUASAN DAN LOYALITAS PELANGGAN INDUSTRI KAYU PERHUTANI - Winarni Saftarya Timedina Gultom; Lilik Noor Yuliati; Setiadi Djohar (Jurnal Manajemen & Agribisnis, 2016)
The purpose of this research is to analyze the influences of service quality, product quality and perceived value on the satisfaction and loyalty of the customers of Perhutani wood industry, the level of customer satisfaction and loyalty and managerial implications. Four data analysis techniques were used including the structural equation modeling partial least squares (SEMPLS) with 24 exogenous latent variable attributes and 6 endogenous latent variable attributes; CSI, CLI and IPA. SEMPLS results showed that the variables of service quality (T-statistic=2, 79*>T-table=1, 96) and product quality (T-statistic=6, 45*>T-table=1, 96) significantly influence the satisfaction of the customers of Perhutani wood industry. Perceived value variable (T-statistic=0, 65<T-table=1, 96) doesn’t influence significantly in the form of customers satisfaction. Customer satisfaction (T-statistic=1, 53<T-table=1, 96) does not significantly influence the customer loyalty. The data of CSI=80, 85% and CLI=74, 12% indicate the customers are satisfied and loyal to the service quality, product quality, and perceived value provided by Perhutani wood industry. The main priority of the performances to be improved based on IPA include the attributes of accuracy of product sizes: length, width, thickness), complaint handling, product delivery, service employees, comprehension of needs, officer awareness, information on the documents and prevailing prices, service time completion, purchase document accuracy, price certainty, allocation certainty, suitability prices with quality, and affordable product prices.Keywords: perhutani, wood industry, satisfaction, loyalty, SEMPLS